Anti-Tumor Necrosis Factor Receptor 2 Antibody Combined With Anti-PD-L1 Therapy Exerts Robust Antitumor Effects in Breast Cancer - Fu, Qiang; Shen, Qian; Tong, Jin; Huang, Liu; Cheng, Yi; Zhong, Wei (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer is the most common female malignant tumor and a public health challenge in the world. In this study, we demonstrate that tumor necrosis factor receptor 2 (TNFR2) is highly expressed in both breast tumor tissue and by tumor-infiltrating immunosuppressive CD4+CD25+FoxP3+ regulatory T cells (Tregs). We show dose-escalating concentrations of a TNFR2 antagonistic antibody reduced the inhibitory effect of Tregs on CD4+CD25- T cells (Teffs). Anti-TNFR2 therapy inhibits 4T1 tumor growth in vivo, elongates tumor bearing mice survival and develop 4T1-specific immune response. Moreover, our data indicates anti-TNFR2 antibody combined with anti-PD-L1 therapy exert more efficiently than anti-TNFR2 or anti-PD-L1 therapy single agent treatment. This research suggests TNFR2 antagonism could potentially offer a clinical benefit as a single agent and/or in combination with anti-PD-L1 treatment in breast cancer therapy.